4a^8 - 28a^4b^5 + 49b^10
Let x = 2a^4 and y = 7b^5
Now you have:
x^2 - 2xy + y^2
(x - y)^2
so, putting the original values back in...
(2a^4 - 7b^5)^2
Just as a note... (2a^4 - 7b^5)^2 yields the same result as (7b^5 - 2a^4)^2, so either are correct.
=====
Why, thank you, Will M. I'm honored to be called a freak for figuring that problem out. :-)
2007-03-30 08:14:38
·
answer #1
·
answered by Mathematica 7
·
3⤊
0⤋
49b^10 + 4a^8 - 28a^4b^5
this should be rewritten as
4a^8 - 28a^4b^5 + 49b^10
(2a^4 - 7b^5)(2a^4 - 7b^5)
or just
(2a^4 - 7b^5)^2
2007-03-30 08:44:26
·
answer #2
·
answered by Sherman81 6
·
0⤊
0⤋
=(7b^5-2a^4)^2
2007-03-30 08:31:34
·
answer #3
·
answered by ironduke8159 7
·
0⤊
0⤋
(7b^5-2a^4)(7b^5-2a^4) or you could write it like (7b^5-2a^4)^2
2007-03-30 08:21:08
·
answer #4
·
answered by hrhbg 3
·
1⤊
0⤋
(7b^5-2a^4)^2
2007-03-30 08:20:51
·
answer #5
·
answered by LemonButt 3
·
1⤊
0⤋
the person who answered this before me is a goddamn freak.
2007-03-30 08:18:11
·
answer #6
·
answered by will m 1
·
1⤊
2⤋